The effects of artificial intelligence on competitive sports - Pu, Q. (Clark University, 2021)
This research thesis is to explore the application and impact of artificial intelligence in the field of competitive sports, discover the risks and problems in it, and discuss solutions. Nowadays, artificial intelligence has been applied to all walks of life, and the field of competitive sports is no exception, such as VR video technology, artificial intelligence for competition and player data analysis, artificial intelligence equipment to help players train, artificial intelligence to develop tactics, etc. But artificial intelligence has also brought about problems such as disrupting game viewing, making intellectual competitive sports meaningless, and threatening the status of industry practitioners. Many people worry that artificial intelligence will bring many uneliminated negative effects to competitive sports, but this is not the case. By referring to news and literature, conducting online questionnaires and interviews with industry practitioners, after discussion and analysis, conclusions were reached. Artificial intelligence has brought innovation and influence on the competitive sports industry. The positive impact it brings far exceeds the risks and problems. At the same time, these negative problems can be solved by artificial control. The application of artificial intelligence will continue to deepen in the competitive sports industry and promote the better development of competitive sports.